Enzymatic production of biodiesel from cotton seed oil using t-butanol as a solvent - Royon, Daniela Beatriz; Daz, Mirta Elizabeth; Von Ellenrieder, Guillermo Rodolfo; Locatelli, Silvano (Bioresource Technology)
The enzymatic production of biodiesel by methanolysis of cottonseed oil was studied using immobilized Candida antarctica lipase as catalyst in t-butanol solvent. Methyl ester production and triacylglycerol disappearance were followed by HPLC chromatography. It was found, using a batch system, that enzyme inhibition caused by undissolved methanol was eliminated by adding t-butanol to the reaction medium, which also gave a noticeable increase of reaction rate and ester yield. The effect of t-butanol, methanol concentration and temperature on this system was determined. A methanolysis yield of 97% was observed after 24 h at 50 °C with a reaction mixture containing 32.5% t-butanol, 13.5% methanol, 54% oil and 0.017 g enzyme (g oil)-1. With the same mixture, a 95% ester yield was obtained using a one step fixed bed continuous reactor with a flow rate of 9.6 ml h-1 (g enzyme)-1. Experiments with the continuous reactor over 500 h did not show any appreciable decrease in ester yields. © 2006 Elsevier Ltd. All rights reserved. Fil: Royon, Daniela Beatriz. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Salta. Instituto de Investigaciones para la Industria Química. Universidad Nacional de Salta. Facultad de Ingeniería. Instituto de Investigaciones para la Industria Química; Argentina Fil: Daz, Mirta Elizabeth. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Salta. Instituto de Investigaciones para la Industria Química. Universidad Nacional de Salta. Facultad de Ingeniería. Instituto de Investigaciones para la Industria Química; Argentina Fil: Von Ellenrieder, Guillermo Rodolfo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Salta. Instituto de Investigaciones para la Industria Química. Universidad Nacional de Salta. Facultad de Ingeniería. Instituto de Investigaciones para la Industria Química; Argentina Fil: Locatelli, Silvano. Consejo Nacional de ...